The effect of retail mergers on prices and variety: An ex-post evaluation - Elena Argentesi; Paolo Buccirossi; Roberto Cervone; Tomaso Duso; Alessia Marrazzo (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2016)
Unlike most retrospective merger studies that only focus on price effects, we also estimate the impact of a merger on product variety. We use an original dataset on Dutch supermarkets to assess the effect of a merger that was conditionally approved by the Dutch Competition Authority (ACM) on prices and the depth of assortment. We find that the merger did not affect prices but it led the merging parties to decrease the depth of their assortment, thereby reducing consumer choice. This effect is mainly driven by a reduction in variety for stores that were not re-branded after the merger, suggesting that the merging firms reposition their product offerings in order to avoid cannibalization. We also find that the reduction in variety for the merging parties is partially compensated by competitors increasing variety, except in very concentrated markets where all firms decrease variety. The issuance of divestitures partially outweighed the negative effect of the merger. Yet, it appears that additional divestitures would have been necessary to remove completely the adverse effect of the merger on the depth of assortment.
Keywords: L1; L41; L66; L81; D22; K21; C23; 330; Mergers; Variety; Ex-post Evaluation; Retail sector; Supermarkets; Grocery